PRODUÇÃO DE SHAMPOO ESFOLIANTE E ANTIFÚNGICO PARA TRATAMENTO DE DERMATITE SEBORREICA - CASTRO, Denise Frazão (2024)
The objective of the present study was to produce and patent an exfoliating and antifungal shampoo, obtained from the hydroalcoholic extract of Citrullus lanatus (watermelon) seeds, developed at the Federal University of Maranhão, as a therapeutic alternative for the treatment of seborrheic dermatitis. To primary prove the safety and efficacy of the shampoo, in vitro studies of ocular irritability (hemolysis test) and antimicrobial activity were carried out by determining the Minimum Inhibitory Concentration - MIC and Minimum Fungicide Concentration - CFM against yeasts isolated from the scalp of patients with clinical signs of seborrheic dermatitis; and to prove the novelty (patentability requirement), prospective studies were carried out in national and international patent databases and scientific articles. The results obtained in this research demonstrated the in vitro efficacy of the shampoo at 2.5% of the hydroalcoholic extract of Citrullus lanatus seeds, by proving its antimicrobial activity against 62.5% of the clinical isolates tested, with an MIC of 12.5 mg/mL, presenting the characteristic of being fungistatic; The shampoo did not demonstrate hemolytic activity at all concentrations tested. The results of prospective studies did not demonstrate records that would harm the novelty of the developed product, and in view of such results and the primary in vitro proof of safety and efficacy, patent production was carried out and submitted to the National Institute of Intellectual Property (INPI).